1988
DOI: 10.2307/3899377
|View full text |Cite
|
Sign up to set email alerts
|

Justification for Grazing Intensity Experiments: Analysing and Interpreting Grazing Data

Abstract: Grazing trials in which treatments are compared at only 1 gruing intensity greatly outnumber those in which treatments are compared at several grazing intensities. This suggests that, compared to other treatments and the need for replication in grazing trials, researchers consider grazing intensity lower in priority. In this study, a regression modeling approach for analyzing and interpreting data was developed to enhance the vahte of grazing intensity trials. As an example, results from 5 irrigated bermudagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…These findings are in disagreement with those of other studies in which the relationship between ADG and stocking rate was linear (Mezzadra et al, 1992; Bransby et al, 1988; Hart, 1972; Bryant et al, 1965; Petersen et al, 1965; Riewe et al, 1963; Riewe, 1961), although Ashley (1993) and Oberholster (1990) also reported a quadratic relationship between ADG and stocking rate for annual ryegrass pastures and also for cereal rye ( Secale cereale L.).…”
Section: Resultscontrasting
confidence: 82%
“…These findings are in disagreement with those of other studies in which the relationship between ADG and stocking rate was linear (Mezzadra et al, 1992; Bransby et al, 1988; Hart, 1972; Bryant et al, 1965; Petersen et al, 1965; Riewe et al, 1963; Riewe, 1961), although Ashley (1993) and Oberholster (1990) also reported a quadratic relationship between ADG and stocking rate for annual ryegrass pastures and also for cereal rye ( Secale cereale L.).…”
Section: Resultscontrasting
confidence: 82%
“…Replication of treatments was not attempted initially, because the inevitable differences between replicates would consume resources that could otherwise be allocated to increasing the range of treatments. Bransby et al (1988) described the use of a regression modeling approach for the analysis of unreplicated, multiple treatment grazing trials, based on a proposal by Riewe (1961) . .…”
Section: Discussionmentioning
confidence: 99%
“…This regression approach is more powerful statistically than replicated ANOVAbased designs, and allows for research that is more relevant to both management and predictive ecology, by assessing how the effects of the treatment vary with level of the treatment (Cottingham, Lennon, & Brown, 2005). This regression approach is particularly effective for a broad array of management-scale questions, ranging from effects of grazing to effects of precipitation change (Beier et al, 2012;Bransby, Conrad, Dicks, & Drane, 1988).…”
Section: Grazing Treatmentsmentioning
confidence: 99%